2017
DOI: 10.3389/fpls.2017.00658
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analyses of Embryogenesis-Associated Genes during Somatic Embryogenesis of Adiantum capillus-veneris L. In vitro: New Insights into the Evolution of Reproductive Organs in Land Plants

Abstract: An efficient in vitro regeneration system via somatic embryogenesis (SE) was developed for a fern species Adiantum capillus-veneris. Adventitious shoots, green globular bodies (GGBs) and calli were obtained with the maximal induction rate on the Murashige and Skoog (MS) medium of low concentrations of 6-benzyladenine (BA) (0–1.0 mg/L), 2.0 mg/L BA without 2,4-dichlorophenoxyacetic acid (2,4-D), 0.5 mg/L 2,4-D and 0.5–1.0 mg/L 6-BA, respectively. Cyto-morphological and histological changes in the shoot developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…(2008), in A. thaliana , SERK expression precedes and coincides with early embryogenesis and again these authors considered AtSERK1 as a marker of competence for embryogenesis. Different authors have recognized SERK1 as a positive regulator of somatic embryogenesis in dicots (De Oliveira Santos et al., 2005; Ma et al., 2012; Zhai et al., 2015), monocots (Hu et al., 2005), and conifers (Li et al., 2014; Rupps et al., 2016 and Li et al., 2017a,b). Magnani et al.…”
Section: Role Of Omics (Transcriptome Proteome and Metabolome) In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…(2008), in A. thaliana , SERK expression precedes and coincides with early embryogenesis and again these authors considered AtSERK1 as a marker of competence for embryogenesis. Different authors have recognized SERK1 as a positive regulator of somatic embryogenesis in dicots (De Oliveira Santos et al., 2005; Ma et al., 2012; Zhai et al., 2015), monocots (Hu et al., 2005), and conifers (Li et al., 2014; Rupps et al., 2016 and Li et al., 2017a,b). Magnani et al.…”
Section: Role Of Omics (Transcriptome Proteome and Metabolome) In Tmentioning
confidence: 99%
“…Recently, Li et al. (2017a,b) demonstrate the over-expression of SERK-like genes following biotic and abiotic stresses. It is worthwhile to assume that the stress conditions imposed on the explants for SE induction may activate SERK genes coding for transmembrane SERK proteins capable of signal perception and transduction, giving rise to a cascade of events responsible for change of cell fate from competent cells.…”
Section: Role Of Omics (Transcriptome Proteome and Metabolome) In Tmentioning
confidence: 99%
“…Parallel to the above mentioned gene sequence and function analysis, Li et al (2013) have developed A. capillus-veneris as an experimental system. They not only systematically described the morphological process of this plant ( Li et al, 2013 ), but established a culture system for shoot regeneration ( Li et al, 2017 ). In the assay of gene expression during shoot regeneration from sporophyte tissue, they found that expression of AcLEC1 was not only induced by stresses such as drought and ABA ( Xie et al, 2008 ), but also by cultural conditions ( Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…They not only systematically described the morphological process of this plant ( Li et al, 2013 ), but established a culture system for shoot regeneration ( Li et al, 2017 ). In the assay of gene expression during shoot regeneration from sporophyte tissue, they found that expression of AcLEC1 was not only induced by stresses such as drought and ABA ( Xie et al, 2008 ), but also by cultural conditions ( Li et al, 2017 ). These observations sparked a modified hypothesis about the relationship between the origin of the seed maturation process and the LEC1 gene: LEC1-type HAP3 genes may origin for other functions, as it was induced upon stresses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation